2019
DOI: 10.24061/2413-0737.xxiii.3.91.2019.57
|View full text |Cite
|
Sign up to set email alerts
|

Association between rs3200401 long non-coding RNA MALAT1 gene polymorphism and bladder cancer development

Abstract: Мета роботи -вивчення зв'язку rs3200401-поліморфізму гена довгої некодуючої РНК MALAT1 із розвитком раку сечового міхура в популяції мешканців Сумської області. Матеріал і методи. У дослідженні використано цільну венозну кров 141 пацієнта із перехідноклітинним раком сечового міхура (ПКРСМ) та 100 клінічно здорових осіб без онкологічних захворювань в анамнезі. Визначення розподілу алелів за rs3200401-локусом гена MALAT1 здійснювали за допомогою полімеразної ланцюгової реакції в реальному часі (Real-time PCR) із… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In the present molecular epidemiology study conducted in 1350 OSCC patients and 1199 healthy controls, we found that mutant base T of rs3200401 was significantly associated with a lower risk of OSCC, regardless of the codominant model (TT) or dominant model (CT+TT). Similar to our results, previous studies showed that the risk of prostate cancer (PCa) development in a Ukrainian population was significantly lower in those with the rs3200401 TT genotype compared to CC genotype ( 31 ). In breast cancer, the CT genotype of rs3200401 imparted a lower risk of breast cancer compared to CC in a Han Chinese population ( 20 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present molecular epidemiology study conducted in 1350 OSCC patients and 1199 healthy controls, we found that mutant base T of rs3200401 was significantly associated with a lower risk of OSCC, regardless of the codominant model (TT) or dominant model (CT+TT). Similar to our results, previous studies showed that the risk of prostate cancer (PCa) development in a Ukrainian population was significantly lower in those with the rs3200401 TT genotype compared to CC genotype ( 31 ). In breast cancer, the CT genotype of rs3200401 imparted a lower risk of breast cancer compared to CC in a Han Chinese population ( 20 ).…”
Section: Discussionsupporting
confidence: 92%